EVALUASI EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH KOTA MEDAN: (Studi Kasus di Badan Pengelolaan Pajak dan Retribusi Daerah Kota Medan) - Sembiring, Sabeth; Sinaga, Ria Veronica; Sembiring, Yogi Yovendra (Jurnal Ilmiah Akuntansi (JIMAT), 2023)
This study aims to determine the level of effectiveness and contribution of Customs Tax on Land and Building Rights to the Regional Original Income of Medan City. The population of this study is the Medan City BPHTB tax and Medan City Original Revenue from 1978-2020. The sample of this research is the number of targets and realization of BPHTB tax revenues and realization of PAD in Medan City in 2016-2020. This study uses a descriptive method, the data collection technique in this study is a documentation technique obtained from the Medan City BPPRD office, and analyzes using the formula for the level of effectiveness and the level of contribution. Based on the results of the study, it shows that the level of effectiveness of the Tax on Acquisition of Rights on Land and Buildings has an average of 89.83% overall from 2016-2020 and is classified as "quite effective" and for the level of contribution of Taxes on the Acquisition of Rights on Land and Buildings. 2016-2020 with an average BPHTB tax contribution of 23.02% better than the Contribution Level of Tax Revenue from Land and Building Rights Acquisition in 2011-2015 with an average BPHTB tax contribution of 18.88%.